Mitofusin 2 Promotes Apoptosis of CD4+ T Cells by Inhibiting Autophagy in Sepsis - Ying, Lan; Zhao, Guang-Ju; Wu, You; Ke, He-Liang; Hong, Guang-Liang; Zhang, Hui; Dong, Ning; Wu, Yao; Yao, Yong-Ming; Lu, Zhong-Qiu (Mediators of Inflammation, 2017)
Apoptosis of CD4+ T cells is a primary pathophysiological mechanism of immune dysfunction in the pathogenesis of sepsis. Mitofusin 2 (Mfn2), an integral mitochondrial outer membrane protein, has been confirmed to be associated with cellular metabolism, proliferation, and apoptosis. The function of Mfn2 in CD4+ T cell apoptosis in sepsis is poorly understood. Here, we discovered increased in vivo Mfn2 expression, autophagy deficiency, and elevated cell apoptosis in murine splenic CD4+ T cells after cecal ligation and puncture (CLP). We also observed almost identical results in splenic CD4+ T cells upon lipopolysaccharide (LPS) stimulation in vitro. Furthermore, overexpression of Mfn2 resulted in impaired autophagy and increased apoptosis in Jurkat cells. Pharmacological inhibition of autophagy with 3-methyladenine enhanced Mfn2 overexpression-induced cell apoptosis. In addition, overexpression of Mfn2 downregulated phorbol myristate acetate (PMA)/ionomycin-, rapamycin- and starvation-induced autophagy in Jurkat T cells. Taken together, these data indicate a critical role of Mfn2 in CD4+ T cell apoptosis in sepsis and the underlying mechanism of autophagy deficiency.